Autocatalytic Acetylation of Crude Glycerol Using Acetic Acid: A Kinetic Model - Perez, Federico Martín (2024)
The aim of this work was to develop a kinetic model based on the power law to describe theevolution of glycerol conversion and product distribution in the crude glycerol (G) acetylation reaction with acetic acid (AA) without the use of a catalyst. For this purpose, experimental tests were carried out with analytical glycerol under different reaction conditions (T = 80?160 ◦C, AA/G = 1?9 molar ratio, t = 0.25?2 h). The results showed the formation of mono- (MAG), di- (DAG) and tri- (TAG) acetylglycerols, liquid products with multiple applications in the chemical industry. From these results, a kinetic model based on the power law was implemented, which could acceptably estimate the experimental concentrations with an average relative error of 14.9%. Then, crude glycerol samples from different biodiesel industries were characterized by identifying and quantifying the impurities present in them (H2O, CH3OH, NaOH, NaCOOH, MONG and NaCl), and employed as reactants in the reaction tests. Given the significant differences observed in the glycerol conversion values compared to those obtained with analytical glycerol, further reaction tests were conducted to elucidate the effect of each impurity over the glycerol conversion. In these tests, the different impurities were added individually, maintaining the same concentration range as that of the crude glycerol samples.From the results obtained, global activity factors were introduced, which allowed us to modify thekinetic model to estimate glycerol conversions in the crude glycerol samples with an average relative error of 7%. It is hoped that this kinetic model will be a powerful tool useful for designing reactors on an industrial scale.